Functional anaerobic and strength training in young adults with cerebral palsy - Gillett, J.; Lichtwark, G.; Boyd, Roslyn; Barber, L. (Lippincott Williams & Wilkins, 2018)
Purpose: This study aimed to investigate the efficacy of a 12-wk combined functional anaerobic and strength training program on neuromuscular properties and functional capacity in young adults with spastic-type cerebral palsy. Methods: A total of 17 young adults (21 ± 4 yr, 9 males, Gross Motor Function Classification System I = 11 and II = 6) were randomized to 12 wk, 3 sessions per week, of high-intensity functional anaerobic and progressive resistance training of the lower limbs (n = 8), or a waitlist control group (n = 9). Pre- and posttraining plantarflexor and tibialis anterior muscle volumes and composition, passive and active plantarflexor muscle properties, and functional capacity outcomes were assessed. Results: The training group had higher values compared with the control group (adjusted mean difference) at 12 wk for the following: More- and less-impaired total plantarflexor and tibialis anterior muscle volumes, maximum isometric plantarflexion strength, muscle power sprint test peak power, agility shuttle time, composite functional strength score, and 6-min walk test distance. The change in total plantarflexor muscle volume was associated with the change in plantarflexor muscle strength. There were relationships between the change in plantarflexor muscle strength and the change in functional capacity outcomes (functional strength; 6-min walk test). Conclusions: Combined functional anaerobic and strength training increased muscle size, strength, and functional capacity in young adults with cerebral palsy. The addition of anaerobic training to progressive resistance training programs assists in the transfer to improved functional capacity.